Feedback control of a master bacterial cell-cycle regulator - Domian, Ibrahim J. (The National Academy of Sciences, 1999)
The transcriptional regulator CtrA controls several key cell-cycle events in Caulobacter crescentus, including the initiation of DNA replication, DNA methylation, cell division, and flagellar biogenesis. CtrA is a member of the response regulator family of two component signal transduction systems. Caulobacter goes to great lengths to control the time and place of the activity of this critical regulatory factor during the cell cycle. These controls include temporally regulated transcription and phosphorylation and spatially restricted proteolysis. We report here that ctrA expression is under the control of two promoters: a promoter (P1) that is active only in the early predivisional cell and a stronger promoter (P2) that is active in the late predivisional cell. Both promoters exhibit CtrA-mediated feedback regulation: the early P1 promoter is negatively controlled by CtrA, and the late P2 promoter is under positive feedback control. The CtrA protein footprints conserved binding sites within the P1 and P2 promoters. We propose that the P1 promoter is activated after the initiation of DNA replication in the early predivisional cell. The ensuing accumulation of CtrA results in the activation of the P2 promoter and the repression of the P1 promoter late in the cell cycle. Thus, two transcriptional feedback loops coupled to cell cycle-regulated proteolysis and phosphorylation of the CtrA protein result in the pattern of CtrA activity required for the temporal and spatial control of multiple cell-cycle events.